1964
DOI: 10.1530/acta.0.0450335
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Variations in the Hypophyseal FSH-Content in the Female Rat

Abstract: FSH-estimations were carried out on anterior pituitary glands obtained from rats in four stages of the oestrous cycle: early dioestrus, late dioestrus, pro-oestrus and oestrus. Autopsy was carried out in one experimental series in the morning, in a second one in the afternoon. The combined results suggested a sudden fall in hypophyseal FSH-content about noon on the day of pro-oestrus. This suggestion was confirmed by estimating the FSH-content of anterior pituitary glands removed from pro-oestrous rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1966
1966
1974
1974

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Differences in pituitary FSH content between different groups of females were similar to those observed in rats, although these results are more detailed (Ladman & Runner, 1953;Gans & de Jongh, 1963;Gans, de Jongh, van Rees, van der Werff ten Bosch & Wolthuis, 1964;Parlow, 1964;Kobayashi, Kobayashi, Tsuyuguchi & Nagai, 1965). It is generally believed that gonadotrophin is released in the afternoon, especially on the day of pro-oestrus, and that high levels in the pituitary are indicative of high levels of production and possibly release.…”
Section: Discussionsupporting
confidence: 56%
“…Differences in pituitary FSH content between different groups of females were similar to those observed in rats, although these results are more detailed (Ladman & Runner, 1953;Gans & de Jongh, 1963;Gans, de Jongh, van Rees, van der Werff ten Bosch & Wolthuis, 1964;Parlow, 1964;Kobayashi, Kobayashi, Tsuyuguchi & Nagai, 1965). It is generally believed that gonadotrophin is released in the afternoon, especially on the day of pro-oestrus, and that high levels in the pituitary are indicative of high levels of production and possibly release.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, LH-RF in the median eminence showed the highest level in the afternoon of pro-oestrus and the lowest in the morning of oestrus (RAMIREZ and SAWYER, 1965). As regards FSH, it was reported that pituitary FSH content rapidly decreased in the late afternoon of pro-oestrus as in the case of LH (GANS et al, 1964;CALIGARIS et al, 1967;MCCLINTOCK and SCHWARTZ, 1968;GOLDMAN and MAHESH, 1968;NEGRO-VILAR et al, 1970). At the same stage plasma level of FSH was higher than in the other stages (MCCLINTOCK and SCHWARTZ, 1968).…”
Section: Changes In the Female Pituitary During The Oestrous Cyclementioning
confidence: 93%
“…The assay methods for the determination of FSH in blood are not suf¬ ficiently sensitive for this purpose and some doubt on the validity of claims to have determined the level of LH in the peripheral blood of cycling animals has been raised by the work of Pelletier (1965). The amounts of these gonadotrophic hormones in pituitary glands have been determined and results obtained with assay methods specific for FSH and LH in the sheep (Santolucito, Clegg & Cole, 1960;Robertson & Hutchinson, 1962), rat (Schwartz & Bartosik, 1962;Gans, de Jongh, Van Rees, Van der Werff ten Bosch & Wolthuis, 1964), and cow , suggest that a massive release of both FSH and LH occurs before ovulation. * Present address : Veterinary Department, Ministry of Agriculture, Dokki, Cairo, U.A.R.…”
Section: Introductionmentioning
confidence: 99%